VD_FINDINFO Jug / 2019 / 58 vom 28. August 2018 - VD Tribunal cantonal (2018)
VOIES DE FAIT, INJURE, MENACEDROIT PÉNAL, CONTRAINTEDROIT PÉNAL | 106 CP, 126 al. 1 CP, 126 al. 2 let. b CP, 177 CP, 180 al. 1 CP, 180 al. 2 let. a CP, 22 ad 181 CP, 44 al. 1 CP, 44 al. 2 CP